Effect of zinc oxide nanoparticles embedded NPK fertilizer on growth, yield and zinc concentration and uptake of aromatic rice (Oryza sativa) - BARAL, KIRTTIRANJAN; KUMAR, DINESH; SHIVAY, YASHBIR SINGH (The Indian Journal of Agricultural Sciences, 2020)
Application of ZnO nanoparticles in conjunction with NPK fertilizers helped in increasing growth parameters, enhancement in Zn concentration in rice grain and straw and also grain yield and could save a significant amount of nutrients. As highest grain yield was recorded with application of 100% NPK + 7.5 g ZnO Nps/ha which was statistically at par with 75% NPK + 7.5 g ZnO Nps/ha, hence it can be concluded that application of 75% NPK + 7.5 g ZnO Nps/ha is best as it required 25% less NPK. Likewise, ZnO nanoparticles application had a significant effect on Zn concentrations. Therefore, it can be inferred that ZnO nanoparticles application embedded with NPK fertilizer can save nutrients, increase nutrient concentration and also profit can be accrued due to less requirement of nutrients than recommended dose of fertilizers.